Assessment of Caries Risk Using Salivary Biomarkers and Clinical Parameters in Pediatric Patients - Dr.P.R.SANJAYA M.D.S. (The Bioscan, 2025)
Dental caries remains one of the most prevalent chronic conditions among children worldwide, reflecting a complex interplay between host factors, microbial ecology, diet, and salivary composition. Traditional risk assessment methods relying solely on clinical and dietary parameters often fail to predict disease onset accurately in pediatric populations. This study aims to evaluate the diagnostic utility of salivary biomarkers alongside clinical parameters to develop a more comprehensive, objective, and early predictive framework for caries risk assessment in children. A cross-sectional analytical study was conducted among pediatric patients aged 5 to 12 years, categorized into caries-free, moderate-risk, and high-risk groups based on the Decayed, Missing, and Filled Teeth (DMFT/dmft) index. Unstimulated whole saliva samples were collected under standardized conditions, and biochemical analyses were performed to quantify salivary flow rate, pH, buffer capacity, total protein concentration, calcium, phosphate, and levels of specific biomarkers, including lactoferrin, α-amylase, secretory IgA, and Streptococcus mutans count. Clinical parameters such as plaque index, dietary habits, and oral hygiene practices were also evaluated and correlated with biochemical findings using multivariate regression models. The results demonstrated a statistically significant association between elevated bacterial load, reduced salivary flow, and lower buffer capacity with higher caries activity. Among the biomarkers, lactoferrin and secretory IgA exhibited notable variations, indicating their potential as early predictors of caries susceptibility. Salivary calcium and phosphate levels were inversely correlated with caries severity, underscoring their protective role in enamel remineralization. The combined assessment of salivary and clinical parameters enhanced the predictive accuracy of caries risk models by nearly 30% compared to conventional diagnostic indices alone. These findings affirm that salivary biomarkers, when interpreted in conjunction with clinical data, offer a powerful, non-invasive, and reproducible method for assessing caries risk in pediatric patients. The incorporation of biomarker-based screening into routine pediatric dental examinations could enable clinicians to identify at-risk children earlier, individualize preventive care strategies, and monitor the efficacy of intervention programs. This integrative approach aligns with precision dentistry principles, promoting a shift from restorative to preventive and personalized oral health management in pediatric populations. KEYWORDS: Caries risk assessment, Salivary biomarkers, Pediatric dentistry, Secretory IgA, Streptococcus mutans